CASE STUDY ON MODERNIZATION TRANSFORMATION AND PERFORMANCE IMPROVEMENT OF PAPER PRINTING INDUSTRY - Jung Chen, Li; Chiuan Lin , Chin (Graduate Program of Universitas Tarumanagara, 2025)
After the COVID-19 pandemic, global economic growth slowed down in 2022. Although Taiwan was affected, its competitiveness remained strong. According to data from the Ministry of Economic Affairs, there are more than 1.63 million small and medium-sized enterprises in Taiwan, accounting for more than 98% of all enterprises, a record high; the number of employees in small and medium-sized enterprises is 9.132 million, accounting for 80% of the national employment, and its sales exceed 28 trillion NTD, accounting for more than 50%, and the export volume is 3.6 trillion NTD, with an annual growth rate of more than 7%, showing the importance of small and medium-sized enterprises in Taiwan's economic development. Since 2021, many industries have been crying out for a shortage of workers. Taiwan's low birth rate is severe, and the COVID-19 epidemic has also led to a serious shortage of workers in various industries. It is a common problem for traditional industries to